Particular paraclinical indices in newborn sepsis patients whose parents constantly lived in different environmental conditions - Olena Vasylivna Vlasova (Journal of Education, Health and Sport, 2020)
Xenobiotics can have a variety of effects on the human body, and especially on the course of intrauterine development. Numerous researchers point out that it is the nature of the environment that can negatively affect the course of certain diseases in both children and adults. Neonatal sepsis is one of the most serious diseases in neonatology practice. And, in our opinion, the topic of the influence of adverse environmental factors on the features of sepsis in newborns depending on the ecological situation of their parents' habitats is unclarified. The research aims at the particular paraclinical indices in children with neonatal sepsis whose parents constantly lived in different environmental conditions. Material and methods. To study the aim, a comprehensive survey of 260 newborns who suffered from neonatal sepsis in 2016-2018 was conducted. The groups have been formed based on the complex evaluation of the prolonged influence of the anthropogenic pollution of air, water and soil on the body of parents of newborns in the parts of the region. The ecological risk coefficient (ERC) has been proposed concerning the environmental situation in the regional centers. Thus, the first clinical group (the main group) included neonatal sepsis patients whose parents permanently lived in parts with an ERC of 2.0 or more and with unfavorable environmental characteristics of the regional center. The second group (comparison) was formed by newborns with sepsis, whose parents permanently lived in areas with a low risk of adverse effects of these environmental factors on their body (ERC<2.0). Results and discussion. The content of interleukins-6, -8.-10, C-reactive protein, presepsin and procalcitonin in the blood serum of patients with neonatal sepsis showed the activity of the systemic inflammatory response of the body to an infectious agent. It should be noted that high serum levels of interleukin-10, which has an anti-inflammatory effect, was more often registered in patients of the I clinical group. Thus, the blood content of this interleukin 35.0 pg/ml occurred in the newborn of the main group in 23.7% of cases, and in children of the comparison group – in 18.1% of observations. Along with a clearer identification of high levels of anti-inflammatory interleukin-10 inpatients of the I group, a significant decrease in serum concentrations of immunoglobulins of classes A, G, M was observed in these newborns. Conclusions. The decrease in the level of the above serum immunoglobulins is probably due to the immunosuppressive effect of xenobiotics on the fetus, whose mother was under the conditions of long-term action of xenobiotics. This, in turn, reduces the resistance of the newborn body to infection and contributes to a more severe course of the infectious process. Probably, the more severe manifestations of neonatal sepsis in newborns of the I clinical group are partly due to a combination of decreased immunoglobulin synthesis and increased interleukin-10 production.